Analytical validation of a portable human Accu-Chek glucometer in honeybee hemolymph. (September 2022) - Cournoyer, Antoine; Deschamps, Annie; Bau-Gaudreault, Liza; Dubreuil, Pascal; Benoit-Biancamano, Marie-Odile
Glucose and trehalose are the main energy sources used by honeybees ( Apis mellifera ) for daily activities. However, there is no validated point-of-care method to reliably measure both sugars. We performed an analytical validation of a portable human glucometer (Accu-Chek; Roche) for glucose measurement in honeybee hemolymph compared to a reference method (GluCH, UniCel DxC 600; Beckman Coulter). We used 30 pooled hemolymph samples collected from the antennae of anesthetized honeybees and diluted 1:4 in 0.9% saline. We evaluated dilution linearity, spike recovery, and inter- and intra-assay imprecision. Glucose concentration was measured over time (2 h, 4 h, 8 h, 12 h, 1 d, 2 d, 3 d, 7 d, 21 d, 28 d) at various storage temperature (25°C, 4°C, −20°C, −80°C). The trehalose concentration was measured indirectly by trehalase hydrolyzation. Glucose concentrations measured by both instruments had a strong correlation (0.985, p  < 0.0001) and a bias of −7.33 mmol/L (±1.96SD: 13.70 to −28.36), with linear agreement at <20 mmol/L (physiologic value: 100 mmol/L). The accuracy of the glucometer decreased at >20 mmol/L. Recovery of 115–130% of diluted spikes indicated good specificity. Inter- and intra-assay imprecision were 2.50% and 2.21%, respectively. Glucose concentrations fluctuated in stored samples dependent on time and temperature; however, glucose concentrations were constant with storage at −80°C for ≥28 d. The Accu-Chek glucometer is an adequate instrument to measure honeybee glucose concentration in hemolymph diluted with 0.9% NaCl, with good accuracy and precision at <20 mmol/L. Hemolymph storage at −80°C is suitable for long-term conservation of glucose.